Resilience of wild and cultivated bitter melon (Momordica charantia) under deficit irrigation in Vietnam - THUAN VAN NGUYEN; MUSLIAR KASIM; TUTY ANGGRAINI; LINH NHUT DOAN; NHA VAN DUONG (Biodiversitas Journal of Biological Diversity, 2025)
Abstract. Nguyen TV, Kasim M, Anggraini T, Doan LN, Duong NV. 2025. Resilience of wild and cultivated bitter melon (Momordica charantia) under deficit irrigation in Vietnam. Biodiversitas 26: 5248-5257. Water scarcity increasingly constrains vegetable production in tropical regions, requiring adaptive strategies such as deficit irrigation and the use of resilient genetic resources. This study evaluated the physiological and agronomic responses of two Momordica charantia accessions—designated as the wild type (TCCS VP-BT08/16) and the cultivated type (TCCS VP-BT01/14)—under three irrigation regimes (80 %, 65 %, and 50 % of field capacity, FC) in a split-plot field experiment conducted during the 2024–2025 dry season in Vietnam. Growth traits, SPAD chlorophyll values, and cumulative dry fruit yield were assessed using ANOVA and Duncan's multiple range test (P < 0.05). Irrigation significantly influenced all measured traits (P ? 0.001). The cultivated type showed strong early vigor under full irrigation but declined rapidly after ~90 days under water stress, whereas the wild type maintained stable growth, branching, leaf production, and SPAD values across irrigation levels through 120 days. Dry fruit yield was sustained at 65% FC in both accessions (~185 g plant-¹ wild, ~178 g plant-1 cultivated) without significant reduction from full irrigation, while severe deficit (50% FC) caused moderate yield decline in the wild (~22%) and substantial losses in the cultivated type (~50%). These findings indicate that maintaining soil moisture at 65% FC can sustain bitter melon yield under dry-season conditions and highlight the superior drought resilience of the wild bitter melon as a valuable genetic resource for breeding climate-resilient cultivars.